Pierre Lyonet’s (1706–1789) Study of Insects: Displaying Virtue and Gaining Social Status through Natural History - Scholten, Koen (Studium, 2019)
This paper looks at the gentlemanly natural history practiced by Pierre Lyonet (1706–1789). Eighteenth-century natural history was inextricably linked to social status and Enlightenment ideals such as civility. By looking at the social network Lyonet built, we can reconstruct how past-time naturalists could enter the Republic of Letters, learned societies, and what this meant in the wider culture. For Lyonet, his study of insects had profound moral, religious and patriotic dimensions. This political and societal embeddedness enabled Lyonet to be both a benefactor to the state’s “public good”, meet the standards of a gentleman, while at the same time adhering to politesse in the Republic of Letters. All in all, this paper presents Lyonet as a gentlemanly naturalist working for state and status.